Career movement of graduates of UPV Master's Program (1976-1986). - Tayo, Gilma T.; Zapanta, Lea S.
To assess the relevance and effectiveness of UPV graduate programs in terms of career mobility of its graduates, questionnaires were mailed to UPV master's degree graduates of 1976 up to the present. From 233 responses it was shown that 70
Terminal report. May 1989. Graduate School, UP in the Visayas, Iloilo City
Keywords: Education; UPV Master's Program